Antimicrobial Ionic Liquid‐Based Materials for Biomedical Applications (Adv. Funct. Mater. 42/2021). (14th October 2021) - Nikfarjam, Nasser; Ghomi, Matineh; Agarwal, Tarun; Hassanpour, Mahnaz; Sharifi, Esmaeel; Khorsandi, Danial; Ali Khan, Moonis; Rossi, Filippo; Rossetti, Arianna; Nazarzadeh Zare, Ehsan; Rabiee, Navid; Afshar, Davoud; et al.
Abstract : Antimicrobial Ionic Liquids The antimicrobial effect of ionic liquids (positive and negative charge) could be tuned by tailoring their structural features. In article number 2104148, Eric Lichtfouse, Franklin R. Tay, Pooyan Makvandi, and co‐workers comprehensively discuss the antibacterial activity of ionic liquids in biomedical applications such as wound healing.